TANTANGAN DAN MASALAH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN METODE BLENDED LEARNING DI SDN 02 OGAN JAYA KECAMATAN SUNGKAI UTARA KABUPATEN LAMPUNG UTARA - Sobirin; Renol Abearto; Siti Patimah; Meilisa Sajdah; A. Latief Arung Arafah (Program Studi Manajemen Pendidikan Islam, 2023)
The challenges and problems of learning Islamic religious education are two fundamental aspects that are interrelated in determining The purpose to be achieved in this study is to find out and study more deeply related to the challenges and problems of learning Islamic Religious Education with the blended learning method at SDN 02 Ogan Jaya. Based on the analysis of the data, the results of the study are the implementation of Islamic Religious Education learning with the blended learning method at SDN 02 Ogan Jaya. Ogan Jaya Village, North Sungkai District, North Lampung Regency It still needs to be developed and needs the cohesiveness of educators and students in the learning process. The blended learning-based learning method is very appropriate to be carried out at SDN 02 Ogan Jaya, but it is still constrained by an inadequate internet network, only a few towers stand in a rural area, especially in the village of Ogan Jaya at the location of SDN 02 Ogan Jaya. This study aims to identify the challenges and problems of learning Islamic religious education at SDN 02 Ogan Jaya The results of the study show that the challenges and problems of learning Islamic Religious Education with the blended learning method are very effective and harmonious to be able to overcome these challenges and problems so that a conducive and fun learning environment can be created, thus a quality generation will be formed